A Review of the Comprehensive Recovery of Valuable Elements from Copper Smelting Open-Circuit Dust and Arsenic Treatment - Xu, Bin; Ma, Yongpeng; Gao, Wei; Yang, Junkui; Yang, Yongbin; Li, Qian; Jiang, Tao (JOM (1989), 2020)
Copper smelting open-circuit (CSO) dust contains various valuable metals, such as copper, lead, and zinc, as well as undesirable toxic elements such as arsenic. Thus, the comprehensive recovery of valuable elements from CSO dust is highly significant from both economic and environmental perspectives. In this review, pyrometallurgical, pyrohydrometallurgical and hydrometallurgical processes are evaluated after the presentation of the formation mechanism and characterization of CSO dust. Hydrometallurgical processing is more suitable for treating the dust because of its low energy consumption, high metal recovery, and no secondary pollution. After the introduction of valuable metal recovery by cementation, sulfuration precipitation, and solvent extraction from CSO dust leaching solution, arsenic removal from the solution by lime, sulfides, iron salts, and natroalunite precipitations was reviewed. Arsenical natroalunite has excellent long-term stability, so natroalunite precipitation is very promising for arsenic immobilization.